Adecuación y aplicación del modelo de evaluación EFQM para medir la calidad de la gestión en las II.EE. públicas del distrito de San Pedro de Lloc, de la Ugel Pacasmayo en el 2007. - Becerra Linares, Gelber Winston (2019)
ABSTRACT The total quality is an approach that aims to ensure medium and long-term growth and development of an organization. In the educational field this philosophy represents a new business management system according as its principles radically modify the characteristic elements of the traditional education system. One of the Total Quality Management Models is the EFQM Excellence Model or European Model of Total Quality Management which has been applied by organizations as a reference guide to achieve excellence. In this study, entitled “Adaptation and implementation of the EFQM assessment model to measure the management, quality of public secondary educational institutions in Pacasmayo, San Pedro de Lloc, in 2007” was applied an instrument used to measure the organization management quality of three educational institutions according to the nine criteria of the EFQM Excellence model. The data processing was done using the inductive-deductive method and the analytic-synthetic method. Finally, the conclusion was that the educational institutions did not achieve the score of one thousand points that represents an ideal performance according to the EFQM model. In addition, the weak criteria identified were leadership and social impact. It indicates that these educational institutions need to implement improvement plans to raise their management level.